Vaginal high-grade sarcoma in pregnancy - P. Akametalu; J.M. Barcelon; O. Myint; N.A. Moatamed; B.Y. Karlan; M. Kamrava; J.G. Cohen (Elsevier, 2021)
Background: Vaginal cancer is a rare malignancy making up 1-2% of all female genital tract cancers. Among vaginal cancers, sarcomas constitute 2% of malignant vaginal lesions, with leiomyosarcomas being the most common type of sarcoma. There is a paucity of data to guide treatment of vaginal sarcomas. This case report details a patient diagnosed with a gynecologic sarcoma during pregnancy who is subsequently treated for residual vaginal disease in the postpartum period with local resection and adjuvant vaginal brachytherapy. Case: A 31-year-old gravida 4 para 0 who presented at 22-weeks gestation with vaginal bleeding to an outside hospital and expelled a mass 11 cm in diameter from the vagina during her admission. Findings were consistent with a high grade gynecologic sarcoma. She underwent planned cesarean section at 36 weeks gestational age with uterine pathology showing no sarcoma. At her 3 month postpartum visit she was found to have a 1 cm posterior vaginal wall lesion which was resected and consistent with vaginal sarcoma. She underwent adjuvant brachytherapy. Conclusion: This case demonstrates the challenges with obtaining a correct pathological diagnosis for pregnant patients with vaginal sarcoma during pregnancy. Surgical resection with negative margins remains an important treatment component. Given the low incidence of disease occurrence in pregnancy and rare number of cases reported in literature, further elucidation of timing of delivery and adjuvant treatment is warranted.